Pengaruh Pendidikan Kepemimpinan Dan Peran Guru Terhadap Kepribadian Santri Di Pondok Pesantren Manahijussadat, Lebak-Banten - Idriyani, Jihan; Mukhtarom, Asrori; Abdurrohman, Asep (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
This study aims to (1) Reveal and analyze the influence of leadership education on the personality of students at the Manahijussadat Islamic Boarding School, (2) Reveal and analyze the influence of the role of teachers on the personality of students at the Manahijussadat Islamic Boarding School, and (3) Reveal and analyze the influence of leadership education and the role of teachers on the personality of students at the Manahijussadat Islamic Boarding School. The method used is a quantitative method. The sampling technique used purposive sampling and saturated samples of 82 students of OPPM Manahijussadat. The data collection technique used a questionnaire that had been tested for validity and reliability. Then the analysis technique in descriptive analysis, Prerequisite testing, and hypothesis testing was processed using SPSS version 0.29. The results of the study showed: (1) There is no influence of leadership education on the personality of students at the Manahijussadat Islamic Boarding School as indicated by the results of the t-test in the form of a sig value > 0.05, namely 0.101; (2) There is an influence of the teacher's role on the personality of students at the Manahijussadat Islamic Boarding School, indicated by the results of the t-test in the form of a sig value <0.05, namely 0.007; and (3) There is an influence of leadership education and the role of teachers on the personality of students at the Manahijussadat Islamic Boarding School, indicated by the results of the F-test in the form of sig <0.05, namely 0.01. The coefficient of determination value is 0.204 or 20.4%, this value can be interpreted that the variables of leadership education and the role of teachers simultaneously have a contribution to the influence of changes in the personality of students at the Manahijussadat Islamic Boarding School by 20.4% while 79.6% is influenced by other factors. Thus, this study shows that leadership education and the role of teachers have a simultaneous influence. In contrast, partial leadership education does not have a significant effect on the personality of students at the Manahijussadat Islamic Boarding School and the role of teachers has a significant impact on the personality of students at the Manahijussadat Islamic Boarding School.Keywords: Leadership Education, Role of Teachers, Personality